Comparison of Measured and Predicted Suction Stress in Partially Saturated Compacted Mixtures of Sand and Clay. Issue 5 (31st January 2014) - Pourzargar, A.; König, D.; Heibrock, G.; Datcheva, M.; Schanz, T.
Abstract : We conducted conventional triaxial and uniaxial tensile tests using partially saturated samples of an artificial compacted mixture of kaolin and sand. Test results were analyzed by applying the effective stress principle in partially saturated soils. The results showed that suction stresses derived by triaxial and tensile tests were consistent at saturations >0.1, while the prediction of suction stress from the drying and wetting soil water characteristic curves of the mixture failed. Experimental results indicated that soil structure effects result in differences in upscaling the microscopic interaction effects to macroscopic strength at different suction levels. These soil structure effects seem to differ for shear strength and tensile strength.